Dampak Program KUR Bank Rakyat Indonesia Terhadap Pendapatan UMKM Bidang Kuliner Di BRI Unit Bumi Beringin Kota Manado - Sihombing, Ceria Deviana; Benu, Noortje Marselianie; Kaunang, Rine (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the impact of the People's Business Credit Program (KUR) of Bank Rakyat Indonesia on the income of MSMEs in the Culinary Sector at BRI Bumi Beringin Unit, Manado City. This research was conducted from April to September 2022. The selection of respondents was intentional. Primary data are data obtained from observation of business sources by interviewing through questionnaires to 25 culinary business owners, customers of KUR BRI Bumi Beringin Unit in Wanea District, Manado City and documentation. Secondary data is data obtained through Bank BRI Bumi Beringin Unit, and also obtained through books obtained from local bookstores and the internet through Google Scholar in the form of books, journal articles and theses related to the topic of this research, namely the Impact of the BRI KUR Program on MSME Income. . The results showed that the impact of the BRI KUR Program Bumi Beringin Unit had a positive impact on MSMEs in the Culinary sector in Manado City which was caused by the difference in income received by MSMEs in the culinary sector, the difference that occurred was from the KUR loan capital used which could assist in the development of MSME businesses so that the occurrence of increase in income after using KUR BRI Bumi Beringin Unit, Wanea District, Manado City.